Knowledge Management in Digital Library and Institutional Repository for Supporting Information Literacy - munawaroh, munawaroh (D3 Teknisi Perpustakaan Fakultas Vokasi Universitas Airlangga, 2015)
The Information has not become knowledge until it has a value for the users, that is the reason we need knowledge management (KM) as the contents in digital library and institutional repository. Knowledge management (KM) refers to the tools, technologies, practices and cognitive.Â Knowledge management (KM) is a capability that manages an organizationâs knowledge, systematic processes for acquiring, organizing, sustaining, applying, sharing and renewing both tacit and explicit knowledge to enhance organizational performance and create a value. Digital library and institutional repository is a managed knowledge as a collection in digital format for knowledge information sharing. The objective of this paper is to explain web-based digital library and web-based institutional repository as a knowledge management to assist sharing knowledge information for supporting information literacy. The web-based consists of contents full text information, user friendly searching, and services. This study used web-based of digital library and institutional repository data by searching on internet and it is qualitative descriptive. The judgment is based on whether the contents are fully texted or not fully texted. The fully texted indicates that the contents can support sharing knowledge or the other way around. It shows that the content of digital library and institutional repository for encouraging is to develop information literacy skill. It can be viewed from digital library and institutional repository as an alternative study e-learning that collaborates between teachers, librarians, and people who are capable in knowledge management for supporting information literacy. It can be concluded that digital library and institutional repository must have information literacy